APPLICATION OF DIGITAL MARKETING CONCEPTS TO INCREASE SALES AND MARKET EXPANSION OF MSME LOCAL PRODUCTS (International Journal of Innovative Technologies in Economy, 2025)
Even with the digital world moving at breakneck speed, many Micro, Small, and Medium Enterprises (MSMEs) in Palintang Hamlet still stick to old-fashioned marketing and barely use the internet. Limited knowledge and scarce money or staff make it hard for them to jump into online promotion. This study set out to see whether a short digital-marketing workshop could lift sales and help local products reach new buyers. We used a straightforward number-crunching plan and tested the trainees before and after the session with a simple quiz. Results were run through a basic linear-regression model in SPSS. Findings show that the class boosted the participants understanding and made them more ready to try digital tools in real life. Put simply, the training works and can spark bigger digital shifts among local firms. Now follow-up help from government and education providers is vital so similar projects spread and keep MSMEs competitive online.